Mitochondrial Bioenergetics in the Metabolic Myopathy Accompanying Peripheral Artery Disease - Rontoyanni, Victoria G.; Nunez Lopez, Omar; Fankhauser, Grant T.; Cheema, Zulfiqar F.; Rasmussen, Blake B.; Porter, Craig (Frontiers in Physiology, 2017)
Peripheral artery disease (PAD) is a serious but relatively underdiagnosed and undertreated clinical condition associated with a marked reduction in functional capacity and a heightened risk of morbidity and mortality. The pathophysiology of lower extremity PAD is complex, and extends beyond the atherosclerotic arterial occlusions and subsequent mismatch between oxygen demand and delivery to skeletal muscle mitochondria. In this review, we evaluate and summarize the available evidence implicating mitochondria in the metabolic myopathy that accompanies PAD. Following a short discussion of the available in vivo and in vitro methodologies to quantitate indices of muscle mitochondrial function, we review the current evidence implicating skeletal muscle mitochondrial dysfunction in the pathophysiology of PAD myopathy, while attempting to highlight questions that remain unanswered. Given the rising prevalence of PAD, the detriment in quality of life for patients, and the associated significant healthcare resource utilization, new alternate therapies that ameliorate lower limb symptoms and the functional impairment associated with PAD are needed. A clear understanding of the role of mitochondria in the pathophysiology of PAD may contribute to the development of novel therapeutic interventions.